2014
DOI: 10.1051/0004-6361/201423797
|View full text |Cite
|
Sign up to set email alerts
|

Asteroseismology for “à la carte” stellar age-dating and weighing

Abstract: Context. In the context of the space missions CoRoT, Kepler, Gaia, TESS, and PLATO, precise and accurate stellar ages, masses, and radii are of paramount importance. For instance, they are crucial for constraining scenarii of planetary formation and evolution. Aims. We aim at quantifying how detailed stellar modelling can improve the accuracy and precision on age and mass of individual stars. To that end, we adopt a multifaceted approach where we carefully examine how the number of observational constraints as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
168
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 157 publications
(180 citation statements)
references
References 90 publications
10
168
0
Order By: Relevance
“…Baudin et al (2012) found a similar result in a red giant star observed by CoRoT. Lebreton & Goupil (2014) examined in detail the correlation between model input parameters of the CoRoT target HD 52265. They quantified the anti-correlation of the mass with the initial helium abundance to be ΔY 0 ΔM = −0.58 and also suggested a correlation of the age with the mixing length parameter of ΔAge Δα = +0.13.…”
Section: Analysis Of Model Differencessupporting
confidence: 56%
See 3 more Smart Citations
“…Baudin et al (2012) found a similar result in a red giant star observed by CoRoT. Lebreton & Goupil (2014) examined in detail the correlation between model input parameters of the CoRoT target HD 52265. They quantified the anti-correlation of the mass with the initial helium abundance to be ΔY 0 ΔM = −0.58 and also suggested a correlation of the age with the mixing length parameter of ΔAge Δα = +0.13.…”
Section: Analysis Of Model Differencessupporting
confidence: 56%
“…Free model, mode frequencies, and empirical surface correction (Lebreton) To model the stars we proceeded as explained in Lebreton & Goupil (2014). A Levenberg-Marquardt minimisation was used to adjust the free parameters in the modelling in order to minimise the merit functions per Eq.…”
Section: Notes 1) Modules For Experiments In Stellar Astrophysicsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the signal-to-noise ratios in the observations are high enough, it is possible to isolate the individual peaks in the power spectrum and perform what is known as "boutique" modelling of the targets (e.g., Lebreton & Goupil 2014;Metcalfe et al 2010;Silva Aguirre et al 2013). In these cases, instead of fitting for the global asteroseismic parameters the Bayesian schemes aim at reproducing either the individual frequencies of oscillations or combinations of them.…”
Section: Improvements For Dwarfs and Subgiants: Individual Frequenciesmentioning
confidence: 99%